Analisis Location Quotient (LQ) Dalam Penentuan Lokasi Basis Perikanan Tangkap/Laut Di Kabupaten Aceh Timur - Humaira, Zulya; Saragih, Faoeza Hafiz; Mahyudin, Thursina (Jurnal Penelitian Agrisamudra, 2025)
The aim of this research is to determine the location of the capture fisheries base in East Aceh Regency using location quotient analysis. The data analysis technique uses location quotient and shift share analysis. From the data analysis, it was found that from the LQ analysis it could be explained that the LQ value for all sub-districts which are areas of captured fish production have LQ values < 1. This indicates that fish production in these sub-districts needs to supply fish from other areas because these sub-districts are not yet able to meet fish needs independently. From the shift share analysis, it is known that Idi Rayeuk District has the highest and positive shift share value, namely 714.51, which means that the capture fisheries sector in Idi Rayeuk District has the largest contribution to the East Aceh fisheries sector. The subdistricts that provided the next highest positive contribution after Idi Rayeuk were Darul Aman subdistrict and Peureulak subdistrict with a shift share value of 54.45 and the shift share value in Peureulak subdistrict was 53.64.